Positive Solution for a Class of Infinite Semipositone (p,q)-Laplace System
In this paper we consider following (p,q)-Laplacian system { aligned & -Δ _pu=λ l( x) u^p-1-f_1( u,v) -au^-α _1 v^β _2 in Ω , & -Δ _qv=μ k( x) v^q-1-f_2( u,v) -bu^α _2 v^-β _2 in Ω , & u=v=0 on Ω , aligned . where Ω is a bounded domain in R^N with smooth boundary Ω , λ and μ are a positive parameters and a, b are a positive constant. By using the method of sub-supersolution we discuss the existence of positive solution., number=4, journal=Discontinuity, Nonlinearity, and Complexity, author=Zeditri, Sounia and Akrout, Kamel and Guefaifia, Rafik, year=2026, month=Aug., pages=757–765